Knowledge and Technologies in Innovative Information Systems 7th Mediterranean Conference on Information Systems, MCIS 2012, Guimaraes, Portugal, September 8-10, 2012. Proceedings - Rahman, Hakikur; Mesquita, Anabela; Ramos, Isabel; Pernici, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 7th Mediterranean Conference on Information Systems, MCIS 2012, held in Guimaraes, Portugal, in September 2012.MCIS 2012 comprised theories, research, and practices based on knowledge management and innovations in organizations, society, and businesses. The 18 full papers presented in this volume were carefully reviewed and selected from 89 submissions. They are organized in topical sections on: emerging and innovative information systems, enterprise systems and enterprise engineering, Web 2.0 enabled business models, information quality management and data accuracy in innovative IS, and ICT applications in healthcare.
Theme 1: Emerging and Innovative Information Systems -- Theme 2: Enterprise Systems and Enterprise Engineering -- Theme 3: Web 2.0 Enabled Business Models -- Theme 4: Information Quality Management and Data Accuracy in Innovative IS -- Theme 5: ICT Applications: The Healthcare Sector.
Keywords: Computer science; Medical records -- Data processing; Information systems; Management information systems; Computer Science; Computer Appl. in Administrative Data Processing; e-Commerce/e-business.; Business Information Systems; Health Informatics; Information Systems Applications (incl. Internet).